Impact of Teacher's Mental State Talk on Young Children's Theory of Mind: A Quasi-Experiment Study - Wu, Jianfen; Liu, Minmin; Lin, Wenqi (Frontiers in Psychology, 2021)
This study investigated the relationship between teachers' mental state talk and young children’s theory of mind with a quasi-experiment. Altogether 56 young children were assigned to the experiment group (Mage = 41 months, SD = 2.47, 46% girls) and the control group (Mage = 40.68 months, SD = 2.23, 43% girls). The experiment group was engaged in a 12-week intervention program with mental state talk in storytelling, casual conversations, and role-playing games, whereas the control group received no interventions. All the children were tested with three theory of mind (ToM) tasks before and after the intervention. The results indicated that the experimental group had a significant improvement in the ToM scores, while the control group showed no significant change. The educational implications of these findings are discussed.